THEORETICAL AND METHODOLOGICAL FOUNDATIONS OF THE MANAGEMENT SYSTEM OF HIGHER EDUCATIONAL INSTITUTIONS (Marketing Journal, 2025)
The article examines the theoretical and methodological foundations of the management system of higher education institutions. An analysis of the main management approaches applicable to the modern model of the university is carried out. The key principles and management tools corresponding to the conditions of digitalization, globalization and growing competition in the educational market are highlighted. The necessity of transition to a hybrid management model combining elements of acade mic autonomy, mark et orientation and network logic is substantiated.
Keywords: management; higher education; theoretical approaches; methodology; university; strategy; digitalization